(untitled) (Journal of Forest and Livelihood, 2018)
The current study was carried out to look at the processes and modality of Bhutan’s national forest inventory; and show the technical ownership of a country towards implementing national forest inventory. Bhutan’s NFI adopted systematic sampling grid of 4 km by 4 km spread across the country and the field surveys were conducted over a period of three and half years to collect data on forest resources. Unlike conventional inventories, Bhutan’s national forest inventory was a multipurpose and holistic forest health monitoring inventory. The entire process was very scientifically and statistically rigorous and robust inventory drawing contributions from various internationally renowned experts and organisations and it is a significant milestone achieved by Bhutan to strengthen institutional capacity, generate information for further research and knowledge and for overall global environmental conservation. Besides, Bhutan’s national forest inventory contributes considerably to Reducing Emissions from Deforestation and Forest Degradation (REDD+) Readiness program of the Royal Government of Bhutan. One of the standout achievements is that current national forest inventory, led by national experts unlike past inventory. As a result, Bhutan has been able to showcase its commitment to environmental conservation, build strong collaboration with government agencies and development partners, strengthen institutional capacity and contribute greatly to knowledge generation and information in the region.